2014
DOI: 10.1039/c3ra45095c
|View full text |Cite
|
Sign up to set email alerts
|

Revoking excited state intra-molecular hydrogen transfer by size dependent tailor-made hierarchically ordered nanocapsules

Abstract: Curcumin associated poly(allylamine hydrochloride) cross-links with dipotassium phosphate and subsequently is assembled with $24 nm SiO 2 nanoparticles to form hierarchically ordered nanocapsule structures, which are 100-1000 nm in size depending on the concentration of dipotassium phosphate. These structures reverse the excited state intra-molecular hydrogen transfer in curcumin depending on the size of the nanocapsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…More interestingly, upon excitation at 338 nm, the emission spectrum of aqueous CC displays a different pattern, which, after deconvolution, reveals two peaks with maximum emission at ∼475 nm and ∼537 nm, assigned to the diketo and enol tautomers, respectively. This assignment is supported by the studies of Mouslmani et al . who observed this second peak of curcumin at ∼456 nm when encapsulated into polyallylamine nanocapsules, and upon excitation at 355 nm.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…More interestingly, upon excitation at 338 nm, the emission spectrum of aqueous CC displays a different pattern, which, after deconvolution, reveals two peaks with maximum emission at ∼475 nm and ∼537 nm, assigned to the diketo and enol tautomers, respectively. This assignment is supported by the studies of Mouslmani et al . who observed this second peak of curcumin at ∼456 nm when encapsulated into polyallylamine nanocapsules, and upon excitation at 355 nm.…”
Section: Resultssupporting
confidence: 68%
“…showed that, with increased temperature and upon excitation at 355 nm, CC exhibits an additional emission peak, blue‐shifted by 73 nm. Both reports ascribed those emissions to a radiative deactivation without undergoing ESHT, namely to the diketo form …”
Section: Resultsmentioning
confidence: 99%
“…This finding motivated us to understand the mechanism of interaction between ASL and curcumin through photophysical analysis. The photophysical properties of curcumin are extensively studied in different solvents and systems like micelles [ 24 27 ], polymeric nanoparticles [ 28 ], cyclodextrin [ 29 31 ], bovine serum albumin [ 32 , 33 ], liposomes [ 34 ], microcapsules [ 35 ], nanocapsules [ 36 ] and polymeric systems [ 37 ]. It is well known that the photophysical properties of this chromophore are linked with the solvent environment and proton donating ability [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although otherwise stated in literature [55] , this is not true for CUR due to its highly symmetric structure.…”
Section: Resultsmentioning
confidence: 97%